Carapanolides M–S from seeds of andiroba (Carapa guianensis, Meliaceae) and triglyceride metabolism-promoting activity in high glucose-pretreated HepG2 cells. Issue 18 (6th May 2015) - Inoue, Takanobu; Matsui, Yuuki; Kikuchi, Takashi; Yamada, Takeshi; In, Yasuko; Muraoka, Osamu; Sakai, Chie; Ninomiya, Kiyofumi; Morikawa, Toshio; Tanaka, Reiko
Abstract: Five novel phragmalin-type limonoids, carapanolides M–Q (1 –5 ), together with two mexicanolide-type limonoids, carapanolides R–S (6 –7 ), were isolated from the oil of Carapa guianensis AUBLET (Meliaceae) seeds, a traditional medicine in Brazil and Latin American countries. Their structures were elucidated on the basis of spectroscopic analyses using 1D and 2D NMR techniques and a single-crystal X-ray diffraction analysis. Compounds1 –7 along with 12 known limonoids, 8 –19, isolated from the flower and seed oil of C. guianensis were assayed to determine their triglyceride metabolism-promoting activities in the high glucose-pretreated human hepatocellular carcinoma cell line, HepG2. Gedunin-type limonoid:14 (% of control at 10 μM: 35.4±3.9), 13 (55.0±3.6 at 10 μM), and18 (75.4±4.2 at 10 μM) significantly reduced TG levels in hepatocytes. Graphical abstract: